Magnetic resonance imaging-guided ultrasound ablation for prostate cancer – A contemporary review of performance - Alabousi, Mostafa; Ghai, Sangeet (Frontiers in Oncology, 2023)
Prostate cancer (PCa) is one of the most common malignancies in men, but patient outcomes are varied depending on extent of disease. Radical, whole-gland therapies, such as prostatectomy or radiotherapy, are definitive treatments for PCa, but they are associated with significant morbidity, including erectile dysfunction and urinary incontinence. Focal therapies for PCa, whereby the part of gland harboring disease is selectively treated, spares the normal surrounding structures, and minimizes the morbidity associated with whole gland treatment. The use of magnetic resonance imaging (MRI) guidance provides advantages, such as better localization and targeting of clinically significant PCa (csPCa), as well as MRI thermometry which optimizes tissue ablation temperatures. This review will discuss two MRI-guided high-intensity focused ultrasound (HIFU) techniques – transrectal MR-guided focused ultrasound (MRgFUS) and TULSA (transurethral ultrasound ablation) ablation for localized PCa. Overall, recent major trials for MRgFUS and TULSA have shown promising oncological and functional results in the treatment of low- to intermediate-risk PCa. Recent Phase II MRgFUS trials have shown better oncologic outcomes than the published results for focal ultrasound guided HIFU and may justify the additional costs associated with MRI guidance. While initial studies on TULSA have focused on subtotal gland ablation, recent trials assessing oncological outcomes for focal treatment of angular sectors have shown promise.